Mencermati Ratio Decidendi Mk Dalam Putusan Nomor 122/Puu-Vii/2009 Tentang Penderogasian Norma Hukum dan Sifat Putusan PTUN - Widodo Ekatjahjana (Jurnal Konstitusi, 2010)
Ratio decidendi of the Constitutional Court that said he was not an organ that has an authority to review constitutional rights loss of applicant, beside contrary to constitutional protection principles, also contrary to functions of the Constitutional Court as the guardian of the constitution, the protector of citizen’s constitutional rights dan the protector of human rights. The Constitutional Court should avoid to put his legal reasoning (in his ratio decidendi) that verdict of administrative court has not a legal nature – erga omnes. He should become aware that an administrative dispute is a public dispute bound under public law principles.